Microbial Biopreparations in Broiler Nutrition: Production, Safety, Quality, and Regulation - Daniela-Mihaela Grigore; Maria-Luiza Mircea; Elena Narcisa Pogurschi (Scientific Papers Animal Science and Biotechnologies)
The increasing global demand for sustainable and high-quality protein sources in poultry production has intensified the exploration of microbial alternatives to conventional feed ingredients. This review provides a comprehensive overview of microbial biopreparations used in broiler nutrition, focusing on their production, composition, functionality, and regulatory considerations. The manuscript begins by addressing the current methods for obtaining biopreparations, with emphasis on fermentation technologies and biomass recovery processes. Special attention is given to microbial protein sources, including single-cell proteins derived from bacteria, algae, and yeasts. Among microbial biotechnology products, yeasts and mixed microbial cultures are discussed as versatile bioresources with high protein content, and potential probiotic benefits. The integration of brewery by-products and brewers’ spent yeast as substrates or feed ingredients is highlighted as a sustainable approach to waste valorisation and circular economy principles. The review further explores the qualitative aspects of microbial biopreparations, such as protein digestibility, bioavailability, and amino acid composition, which are critical for optimizing broiler performance. Safety concerns, including microbial contamination, mycotoxins, and the presence of anti-nutritional factors, are discussed alongside quality assurance practices. The manuscript also outlines the current legal frameworks and international standards governing the use of microbial proteins in animal nutrition, identifying challenges and opportunities for market integration. Lastly, the impact of microbial protein inclusion on broiler health, growth performance, gut microbiota, and immune response is critically evaluated based on recent experimental studies. This review aims to consolidate current knowledge and identify knowledge gaps in the field of microbial biopreparations, supporting their advancement as sustainable and functional alternatives in broiler nutrition.